Effectiveness in double pole propulsion in elite cross-country skiers - Pozzo, R.; Casanova, D.; Scrignaro, N.; Morriconi, B.; Cotelli, C.; Canclini, A. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: In the classical technique of cross country skiing the double pole movement (DP) represents an important mechanism to maintaining the forward CG velocity especially when the inclination of the ground is minimal (Millet 1998, Nilsson 2003). The use of trunk, shoulder and elbow is to be optimised in order to achieve a great amount of horizontal force impulse. This is dependent by a great extent from the actual inclination of the poles with respect to the ground. So, at 45 degrees of inclination the vertical and horizontal components of the pole ground reaction force (Ftot) are equal and the horizontal component becomes greater when the pole is more inclinated. With this in mind, we analysed the pattern of impulse transmission to the GRF during a double pole sprint test executed on ski rollers at maximal racing velocity and repeated consecutively to verify the effects of possible fatigue. Methods: The forces applied to the poles were measured by two strain-gauges force transducer mounted below the pole grip. Calibration of force transducer was taken with 7 standard weights (5-35 kg). The data were recorded via a portable data-logger at 50 Hz and successively transferred to a PC for analyse. For 2-D analysis, a camcorder (SONY 50 Hz) was used by an operator seated on a pick-up car driving at 5 m laterally to the skiing trace. Markers were located on the back ground every 5 m in order to calibrate the moving camera and to obtain an absolute 2-D-reference system. Every 50 m electronic timer provided for laps time and total time. The total length of testing track was 250m, and the slope was 2°. The biomechanical model of the skier consisted of 17 body landmarks, 6 other points were used for the poles and the skis identification. The total centre of mass (CG) and joints range of motion were calculated with respect to the plane of track, and to the corresponding orthogonal direction (vertical direction). Four to six elite skiers of the Italian national team participated to the experiment in different occasions. Subjects were asked to perform 10 times the 250 m testing-DP trial at racing velocity on their own ski rollers. Rest time between trials was 3-5 min. 2D kinematics was carried out and synchronised with the force data during two complete DP cycles (poling phase PP, recovery phase RP) at the 50 m and 200 m markers respectively. This permits to calculate the vertical (Fver) and horizontal (Fhor) components of the pole ground reaction force Ftot and theirs correspondent impulse. Results: Fig 1 shows two different strategies of force distribution during the PP phase at the 50 m marker in the 1st trial for two representative skiers. Subject D produce lower impulse after the first contact with the ground, i.e. until the pole is less inclinated with respect to the ground. As the pole reach the 45° inclination the impulse, especially the horizontal, increase dramatically. Subject S chooses a non differentiate strategy. He plants the pole more "softly" and then pushes on it with increasing force. The vertical impulse of subject S is much more higher than in D, whereby the horizontal impulse is greater in D. Subject D shows a longer total poling time. When the skier`s instantaneous horizontal velocity is related to the force impulses, it is possible to recognise the quality of the poling phase. So, difference in the strategy of force development appear, especially at the level of the 200 m marker, when subjects perform the last trials, i.e. become somewhat tired. Using the time values of the 50 m laps it is possible to describe the development of the average velocity (AVx) for the entire trial (250m). If we compare the variations of AVx with the variations of the Ftot impulse (IFtot) it is possible to calculate an indirect index of effectiveness in the force production, i.e. in the distribution of vertical and horizontal impulses. In order to better compare the skiers, the AVx and IFtot values were expressed as percent of the values obtained at the first 50 m marker. When impulse values decrease of 10% but velocity is reduced more then 10%, then the impulse distribution between horizontal and vertical force was not optimal, and vice versa. Further considerations are taken on kinematic patterns. Variations on angle-angle graphs indicate coordination strategy. Discussion/Conclusions: In order to obtain a good quality of CG propulsion, impulse produced by double poling should match the biomechanical constrains of horizontal linear momentum and the physiological demands for a fine tuning of the muscles groups of lower and upper body. Appling biomechanical tests of different complexity one is able to determine direct as well indirect parameters for better diagnosis and to enhance the efficacy of training methods.